The auxin response factor gene family in banana: genome-wide identification and expression analyses during development, ripening, and abiotic stress - Hu, Wei; Zuo, Jiao; Hou, Xiaowan; Yan, Yan; Wei, Yunxie; Liu, Juhua; Li, Meiying; Xu, Biyu; Jin, Zhiqiang (Frontiers in Plant Science, 2015)
Auxin signaling regulates various auxin-responsive genes via two types of transcriptional regulators, Auxin Response Factors (ARF) and Aux/IAA. ARF transcription factors act as critical components of auxin signaling that play important roles in modulating various biological processes. However, limited information about this gene family in fruit crops is currently available. Herein, 47 ARF genes were identified in banana based on its genome sequence. Phylogenetic analysis of the ARFs from banana, rice, and Arabidopsis suggested that the ARFs could be divided into four subgroups, among which most ARFs from the banana showed a closer relationship with those from rice than those from Arabidopsis. Conserved motif analysis showed that all identified MaARFs had typical DNA-binding and ARF domains, but 12 members lacked the dimerization domain. Gene structure analysis showed that the number of exons in MaARF genes ranged from 5 to 21, suggesting large variation amongst banana ARF genes. The comprehensive expression profiles of MaARF genes yielded useful information about their involvement in diverse tissues, different stages of fruit development and ripening, and responses to abiotic stresses in different varieties. Interaction networks and co-expression assays indicated the strong transcriptional response of banana ARFs and ARF-mediated networks in early fruit development for different varieties. Our systematic analysis of MaARFs revealed robust tissue-specific, development-dependent, and abiotic stress-responsive candidate MaARF genes for further functional assays in planta. These findings could lead to potential applications in the genetic improvement of banana cultivars, and yield new insights into the complexity of the control of MaARF gene expression at the transcriptional level. Finally, they support the hypothesis that ARFs are a crucial component of the auxin signaling pathway, which regulates a wide range of physiological processes.